2008
DOI: 10.1002/eji.200737389
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation, expansion, and monitoring of human iNKT cells with a monoclonal antibody specific for the TCR α‐chain CDR3 loop

Abstract: A significant fraction of CD1d-restricted T cells express an invariant T cell receptor (TCR) a-chain. These highly conserved invariant NKT (iNKT) populations are important regulators of a wide spectrum of immune responses. The ability to directly identify and manipulate iNKT cells is essential to understanding their function and to exploit their therapeutic potential. To this end, we sought monoclonal and polyclonal antibodies specific for iNKT cells by immunizing CD1d KO mice, which lack iNKT cells, with a cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 53 publications
4
77
0
Order By: Relevance
“…Ex vivo identification of natural iNKTa variants in CD1d-restricted ''invariant'' Va24-Ja18/Vb11 TCRs Exley et al have recently published that a significant fraction, up to 30%, of human iNKT-cell clones expressed p93 variants of the ''invariant'' TCR Va24-Ja18 chain [4]. Consistent with this, we identified four different iNKTa variants with single-nucleotide variations at the middle position of codon 93 within the Va24-Ja18 junction from a small panel of 12 ex vivo FACS-sorted human TCR Va241/Vb111 T-cell clones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo identification of natural iNKTa variants in CD1d-restricted ''invariant'' Va24-Ja18/Vb11 TCRs Exley et al have recently published that a significant fraction, up to 30%, of human iNKT-cell clones expressed p93 variants of the ''invariant'' TCR Va24-Ja18 chain [4]. Consistent with this, we identified four different iNKTa variants with single-nucleotide variations at the middle position of codon 93 within the Va24-Ja18 junction from a small panel of 12 ex vivo FACS-sorted human TCR Va241/Vb111 T-cell clones.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have recently shown that the only variable region of human iNKT-cell TCRs, i.e. the CDR3b loop, strongly modulates the affinity to CD1d [3].Human iNKT-cell clones with single-amino acid variations in the ''invariant'' Va24-Ja18 iNKTa chain have been previously identified [4,5], and a recent study found that 4-30% of human iNKT-cell clones carried such variations [4]. However, the effect of these variations on iNKT-cell TCR binding to CD1d has not been examined.…”
mentioning
confidence: 99%
“…Interestingly, a rather substantial proportion of human iNKT cell clones (4-30%), which also express a conserved Vα24-Jα18 rearrangement, has been found with variations to the canonical sequence (37,38). Moreover, these TCR-α variations strongly influenced the affinity of human iNKT TCRs for various antigenCD1d complexes, irrespective of the TCR-β chain with which they were paired (39).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A small population of T cells within this NKT cell subset expresses a highly conserved V␣24J␣18 TCR chain that associates preferentially with V␤11. [16][17][18] These T cells are referred to as invariant NKT (iNKT) cells. Very recently, a novel clonotypic monoclonal antibody 6B11 specific for the V␣24J␣18 TCR chain has been shown to selectively stain human iNKT cells.…”
Section: Invariant Natural Killer T (Inkt) Cells Are Unique T Cells Tmentioning
confidence: 99%
“…Very recently, a novel clonotypic monoclonal antibody 6B11 specific for the V␣24J␣18 TCR chain has been shown to selectively stain human iNKT cells. 18,19 Activation of human iNKT cells requires the presentation of glycolipids, such as ␣-galactosylceramide (␣-GalCer) on the major histocompatibility complex class I-like molecule CD1d. 20 ␣-GalCer stimulation induces rapid cytokine production and potent antitumor and antipathogen responses by iNKT cells.…”
Section: Invariant Natural Killer T (Inkt) Cells Are Unique T Cells Tmentioning
confidence: 99%